What Do You Think You Are Measuring? A Mixed-Methods Procedure for Assessing the Content Validity of Test Items and Theory-Based Scaling - Koller, Ingrid; Levenson, Michael R.; Glück, Judith (Frontiers in Psychology, 2017)
The valid measurement of latent constructs is crucial for psychological research. Here, we present a mixed-methods procedure for improving the precision of construct definitions, determining the content validity of items, evaluation of representativeness of items for the target construct, generating test items, and analyzing items on a theoretical basis. To illustrate the mixed-methods content-scaling-structure (CSS) procedure, we analyze the Adult Self-Transcendence Inventory, a self-report measure of wisdom (ASTI, Levenson et al., 2005). A content-validity analysis of the ASTI items was used as the basis of psychometric analyses using multidimensional item response models (N = 1,215). We found that the new procedure produced important suggestions concerning five subdimensions of the ASTI that were not identifiable using exploratory methods. The study shows that the application of the suggested CSS mixed-method procedure leads to a deeper understanding of latent constructs and shows the advantages of theory-based item analysis.